The Strategies for Strengthening National Geographic Information Infrastructure in Nepal - Subedi, Nab Raj (Journal on Geoinformatics, Nepal, 2010)
Nepal has already initiated the National Geographic Information Infrastructure activities (NGII). For a successful implementation of a National Geospatial Data Infrastructure (NGDI), there is a need for a national policy that will provide the necessary guidelines, identify various committees to be responsible for the various aspects of the NGDI (such as standards, custodianship, sharing and partnership) and provide issues that are acting as the constraints against the take off of the NGDI. The issues must be discussed at a forum where all the stakeholders would meet to discuss on the various issues in the draft policy prior to the approval. There is also a need for an agency to be the lead agency in the development of a NGDI, for which the prevalent NGIIP can be given authority to act as a coordinator until the formation of the National Geographic Information Council. This paper highlights that each stakeholder organization must have certain strategies that work in resonance with broad SDI strategies that perform NGII development and proposes its mission, vision and some general policy statements for the development of SDI activities in Nepal. Some goals and corresponding strategies identified as an outcome of recently held evaluation research on NGII has been provided as an aid for its development.